Peranan Transformasi Perguruan Tinggi Keagamaan Islam dalam Meningkatkan Kualitas Pendidikan Nasional - Yayat Supriyadi; Safuri; Fauzi, Anis; Yogi Damai Syaputra; Deni Iriyadi (Program Studi Manajemen Pendidikan, 2023)
Islamic Religious Universities are higher education establishments that offer education, instruction, and/or development of science, technology, and/or art openly and comprehensibly to the public. Islamic Religious Universities also conduct research and engage in community service, using the findings of their work to advance science, technology, and/or the arts, as well as the welfare of the community. They also organize university management effectively and efficiently, academic administration and general administration in a skilled and transparent manner, and they promote the growth of science, technology, and the arts. Additionally, how are Islamic religious universities' position and function in promoting the growth of. This research is a type of descriptive qualitative research, namely research whose results are written in the form of a series of words, not in the form of numbers. This writing uses the library research method. The role of higher education in a global context is increasingly important in transforming various fields of science, technology and other social institutions to catch up with our country from other developed countries. Higher education is seen as the key to developing science and the quality of people's abilities to seize opportunities for participation in world transformation and sustainable development. Higher education plays a role in developing human potential and abilities needed by their environment